COVID-19 related pressure injuries in patients and personnel: A systematic review. Issue 3 (August 2021) - Yu, Jia-Ning; Wu, Bing-Bing; Feng, Li-Ping; Chen, Hong-Lin
Abstract: Background: Coronavirus disease 2019 (COVID-19) is causing a rapid and tragic health emergency worldwide. Because of the particularity of COVID-19, people are at a high risk of pressure injuries during the prevention and treatment process of COVID-19. Objectives: This systematic review aimed to summarize the pressure injuries caused by COVID-19 and the corresponding preventive measures and treatments. Methods: This systematic review was according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. PubMed, Web of science and CNKI (Chinese) were searched for studies on pressure injuries caused by COVID-19 published up to August 4, 2020. The quality of included studies was assessed by the Newcastle-Ottawa Quality Assessment Scale (NOS) and the CARE guidelines. Results: The data were extracted from 16 studies involving 7, 696 participants in 7 countries. All studies were published in 2020. There are two main types of pressure injuries caused by the COVID-19: 1) Pressure injuries that caused by protective equipment (masks, goggles and face shield, etc.) in the prevention process; 2) pressure injuries caused by prolonged prone position in the therapy process. Conclusions: In this systematic review, the included studies showed that wearing protective equipment for a long time and long-term prone positioning with mechanical ventilation will cause pressure injuries in the oppressed area. Foam dressing may need to be prioritized in the prevention of medical device related pressure injuries. The prevention of pressure injuries should be our particular attention in the course of clinical treatment and nursing. Highlights: During COVID-19 epidemic, medical staff and patients of COVID-19 are at risk of developing pressure injuries. Protective equipment and mechanical ventilation increase the risk of pressure injuries in medical staff and patients. It has a great clinical significance for the prevention and treatment of pressure injuries caused by COVID-19.